Pure White Cell Aplasia and Immune Thrombocytopenia after Thymoma Resection: A Case Report and Review of the Literature. (22nd March 2022) - Youssef, Michael; Stratton, Tyler W.; Gallant, Reid C.; Young, Christine; Li, Daniel Y.; Piran, Siavash
Abstract : We report a case of pure white cell aplasia (PWCA) postthymoma resection in a 74-year-old male presenting with a 2-week history of fevers, night sweats, and severe febrile neutropenia. His pure white cell aplasia was treated with intravenous immunoglobulin (IVIg), granulocyte colony-stimulating factor (G-CSF), prednisone, and cyclosporine with a mixed response. He also developed immune thrombocytopenia, which responded well to a short course of eltrombopag. With continued cyclosporine treatment, his platelet counts were stable after stopping eltrombopag. The patient's cyclosporine treatment was complicated by renal failure, resulting in cessation of cyclosporine. His PWCA and immune thrombocytopenia significantly worsened after stopping cyclosporine, and unfortunately, he died from multiorgan failure and sepsis.